The Moderating Role of Trait Anger in the Relationship between Masculine Stress and Intimate Partner Violence - Dannisworo, Cantyo Atindriyo; Adiningsih, Hana Berliani; Christia, Mellia (UI Scholars Hub, 2019)
There is a high rate of intimate partner violence (IPV) in urban settings. Previous research has found that masculine gender role stress (MGRS) and anger predict IPV. This study aimed to examine the moderating role of anger on the relationship between MGRS and IPV. The sample included 366 urban male college students across Java, who completed an online questionnaire. Measures used were the MGRS-A, BPAQ, and CTS2. Using Hayes’ moderation analysis, the model obtained a significant fit (R2 = .1039, F (3,362) = 13.994, p = .000). Both MGRS (p = .0264) and trait anger (p = .000) predicted IPV. The interaction between MGRS and anger was not significant (p = .0797). However, examination of the conditional effects revealed that there was a significant association between MGRS and IPV at moderate (p = .0264) and high levels of trait anger (p = .0058), but not at low levels of anger. Future studies should investigate the roles of anger expression, control behavior, and anger rumination.